DIGITAL-BASED QUALITY CULTURE RECONSTRUCTION: SPMI TRANSFORMATION TOWARDS SMART ACCREDITATION IN THE 5.0 ERA - Moh. Ainul Yaqin; Muhammad Nafiul Umam (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the reconstruction of a digital-based quality culture through the development of the Smart Accreditation concept as a transformation strategy for the Quality Assurance System (SPMI). The study uses a qualitative approach with a literature review method for various regulations, books, and scientific articles published in the 2016–2026 period. Data were analyzed using content analysis and thematic analysis and validated through theoretical triangulation. The results show that the transformation towards Smart SPMI can gradually shift quality management from a conventional administrative system to an integrated digital ecosystem through Cloud Computing, Artificial Intelligence, Application Programming Interfaces (API), and performance indicator dashboards. This integration can improve data accuracy, accelerate decision-making, reduce administrative burdens, and build a quality culture oriented towards continuous improvement. In addition, the study formulates a conceptual model for Smart Accreditation that integrates digital maturity, transformational leadership, and organizational behavior change to support the sustainability of institutional quality. However, its implementation still faces challenges in the form of infrastructure readiness, human resource digital literacy, data integrity, and organizational cultural resistance. These findings provide conceptual and practical contributions for higher education institutions in building a more adaptive, transparent, and competitive quality assurance system in the Era of Society 5.0.